Experiences with the integration of protocol software tools. - Arvonen, Kari (Computer communications.)
An analysis of a number of protocol software tools that are widely used in the development of communication protocols in the Finnish telecommunications industry is presented. To analyse the integrated use of these tools, a non-trivial application layer protocol with ACSE, ROSE and a simple presentation layer has been designed and implemented with the help of these software tools. Particular attention has been paid to compose a complete protocol implementation from the fragments produced with separate tools. Our observations clearly indicate that this integration is a major problem with the current practices.